Experimental Inoculants and Selection of Ef ficient Native Microorganisms in Slender Black Beans - Echeverría-Pérez, Eric Guillermo; Castañeda-Hidalgo, Ernesto; Robles, Celerino; Santiago-Martínez, Gisela Margarita; Lozano-Trejo, Salvador; Rodriguez-Ortíz, Gerardo; Martinez-Gallegos, Verónica (REVISTA TERRA LATINOAMERICANA, 2025)
The use of biofertilizers made with native soil microorganisms has shown an ef fectiveness in agricultural production similar to that obtained with mineral fertilization. The objective of our research was to evaluate the ef fectiveness of dif ferent experimental inocula based on arbuscular mycorrhizal fungi (HMA) and native nitrogen-fixing bacteria on slender black beans in a greenhouse. The experiment was established in April 2023 with biological material extracted from irrigated and rainfed soils intended for the cultivation of slender black beans in Santa Cruz Lachixolana, Santo Domingo Tlaltinango and Santiago Suchilquitongo, Oaxaca. The evaluation began eight days af ter germination, for eight weeks. For the evaluation of HMA ef fectiveness, the study variables were: RAS index (ratio dry aerial biomass (g)/dry root biomass (g)), relative height growth rate (TRCA, cm/week), rate relative growth in diameter (TRCD, mm/week), leaf area (AF, cm2) and mycorrhizal colonization (MIC, %). To evaluate the ef fectiveness of rhizobia, the variable nodules per plant (NOD, number) was added. The data were analyzed in the SAS version 9.4® sof tware, using an analysis of variance, Bartlett’s homogeneity tests, and separation of means with Tukey test (P ≤ 0.05). The variables evaluated in the HMA inocula recorded highly significant statistical dif ferences between treatments (P ≤ 0.01), the rhizobia inocula evaluated showed highly significant dif ferences (P ≤ 0.01) for the NOD and AF variables. The use of inocula made with native HMA promotes an increase in TRCA, TRCD, AF and MIC by 43, 29, 66 and 60%, respectively, based on the control treatment. The use of rhizobia inocula used as biofertilizers increased the NOD values ​​from 7 to 43 nodules/plant and AF by 82%, both with regards to the control treatment.